Association between Body Mass Index and Spirometric Measurements of Patients with Chronic Obstructive Pulmonary Disease (Medicine Today, 2026)
Introduction: Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality throughout the world. It is a preventable and treatable disease with significant extra pulmonary effects that may contribute to the severity in individual patients. Body mass index (BMI) is an important indicator that can well reflect nutritional status of patients, and low BMI is an independent risk factor for mortality in patients with COPD. The decline in BMI in patients with COPD is a marker of advanced disease. This study is undertaken to investigate the relationship between BMI and pulmonary function of COPD patients. Objectives: To investigate the relationship between BMI and spirometric measurements of COPD patients. Methods: This was an observational descriptive cross-sectional study carried out in inpatient and outpatient Departments of Medicine of Rajshahi Medical College Hospital, Rajshahi, from Dec. 2010 to Dec. 2011. According to inclusion and exclusion criteria, a total of 82 patients diagnosed with COPD, based on history, physical examination and spirometric examination were selected for study. Results: Of the 82 patients, 20(24.39%) were of normal weight, 22(26.82%) were underweight, 25(30.48%) were overweight, 15(18.29%) were obese. FEV1/FVC and FEV1% predicted were lowest in the underweight patients and highest among the obese and overweight patients. A positive correlation between BMI and FEV1/FVC, FEV1% predicted was observed (correlation coefficient (r) was 0.788, 0.802 respectively, both P values were